Main perceived barriers for the development of building service integrated facades: Results from an exploratory expert survey. (September 2017) - Prieto, Alejandro; Klein, Tillmann; Knaack, Ulrich; Auer, Thomas
Abstract: The integration of decentralised building services into façade components presents advantages from functional and constructional standpoints. However, this integrated approach has not been massively implemented, having only stand-alone buildings and façade concepts as examples. This paper seeks to identify the main perceived problems at design, production and assembly stages of the facade development process, to generate new knowledge based on practical experience; and to discuss the perceived barriers to overcome in order to promote widespread building service integration in façade systems. The employed method was an exploratory survey addressed to professionals with practical experience in the development of façade systems for office buildings, situated at any stage of the process. The survey was conducted from mid-September to mid-November 2015 and was distributed both as an online form and in printed format among several professional and research networks related with façade design and construction. After the campaign, 133 questionnaires were received, comprising a final number of 79 valid questionnaires. Results show that the main problems of the overall process are related to coordination issues among different disciplines and stakeholders, while other problems such as costs and lack of knowledge have more impact on particular stages within the design and construction process. Highlights: Process related barriers are perceived as more pressing than product related ones. It is crucial to promote clear communication channels between all stakeholders. The lack of flexibility within the production and supply chain is a major concern. Façade companies have the required experience and maturity to promote innovation. Product development should focus on modularity, both on sizes and connections.